Cybertax : managing the risks and results - Tsantes, George K.; Ransome, James F. (Boca Raton, FL : CRC Press, an imprint of Taylor & Francis Group, 2023)
"The book examines cybersecurity as a tax on the organization and charts the best ways leadership can manage it efficiently. It provides actionable advice on how to adopt an effective cybersecurity posture and recommends treating cybersecurity as a critical business risks"--
Chapter 1. What Is Cybertax?Chapter 2. Cybertax ManagementChapter 3. Cybertax EfficiencyChapter 4. Know Your AdversaryChapter 5. Governing Cybersecurity RiskChapter 6. Solution--CYBERPHOS
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / Security / General; COMPUTERS / Management Information Systems; BUSINESS & ECONOMICS / Strategic Planning; Computer security; Organization